2013
DOI: 10.1007/s00259-013-2343-9
|View full text |Cite
|
Sign up to set email alerts
|

When should we recommend use of dual time-point and delayed time-point imaging techniques in FDG PET?

Abstract: FDG PET and PET/CT are now widely used in oncological imaging for tumor characterization, staging, restaging, and response evaluation. However, numerous benign etiologies may cause increased FDG uptake indistinguishable from that of malignancy. Multiple studies have shown that dual time-point imaging (DTPI) of FDG PET may be helpful in differentiating malignancy from benign processes. However, exceptions exist, and some studies have demonstrated significant overlap of FDG uptake patterns between benign and mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 77 publications
6
147
1
7
Order By: Relevance
“…Thus, while focal hepatic activity with an SUV max of 3.5-4.0 is common on 1-hour PET imaging (and regarded benign), it may be suspicious for malignancy if PET image acquisition was done 2-3 hours after FDG injection. Along with several background tissues (including blood pool, liver, spleen, lungs, pancreas, lymph nodes and skeletal muscle) [13], inflammatory lesions also tend to exhibit decreased FDG activity, while cancers (particularly aggressive, rapidly proliferating cancers) often show increasing FDG activity with increasing radiotracer distribution time [6,14]. These phenomena form the basis for performing dual time-point or delayed PET imaging, which may improve lesion detection and characterization.…”
mentioning
confidence: 99%
“…Thus, while focal hepatic activity with an SUV max of 3.5-4.0 is common on 1-hour PET imaging (and regarded benign), it may be suspicious for malignancy if PET image acquisition was done 2-3 hours after FDG injection. Along with several background tissues (including blood pool, liver, spleen, lungs, pancreas, lymph nodes and skeletal muscle) [13], inflammatory lesions also tend to exhibit decreased FDG activity, while cancers (particularly aggressive, rapidly proliferating cancers) often show increasing FDG activity with increasing radiotracer distribution time [6,14]. These phenomena form the basis for performing dual time-point or delayed PET imaging, which may improve lesion detection and characterization.…”
mentioning
confidence: 99%
“…The granulomas may arise many years after the initial trauma or procedure in the form of tumor-like soft-tissue masses [26][27][28]. Multiple studies have indicated that lesions of active inflammation and infection may have higher 18 FDG activity on DTPI, similar to that in malignant lesions, thus resulting in suboptimal diagnostic performance of DTPI [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Ze względu na powszechną dostępność oraz relatywnie wysoką czułość i swoistość, 18F-FDG PET/CT znalazła szerokie zastosowanie w onkologii jako narzędzie wykrywania nowotworów pierwotnych oraz zmian przerzutowych do tkanek miękkich i kości, oceny przedoperacyjnej guzów oraz monitorowania leczenia [1][2][3][4]. Ponadto, pozytonowa tomografia emisyjna w połączeniu z badaniem tomografii komputerowej umożliwia ocenę charakterystyki biologicznej guza nowotworowego w odniesieniu do budowy anatomicznej analizowanego obszaru [1,5].…”
Section: Wstępunclassified
“…Pomimo, że fluorodeoksyglukoza nie jest znacznikiem swoistym (ang. non tumor-specific) [4,[11][12][13], należy do najczęściej stosowanych radiofarmaceutyków w radioizotopowej diagnostyce onkologicznej.…”
Section: Wstępunclassified
See 1 more Smart Citation